THE ANALYSIS OF THE EFFECT OF DEBT POLICY, DIVIDEND POLICY, INSTITUTIONAL INVESTOR, BUSINESS RISK, FIRM SIZE AND EARNING VOLATILITY TO MANAGERIAL OWNERSHIP BASED ON AGENCY THEORY PERSPECTIVE - DEASY NATHALIA VIDYANTIE; Ratih Handayani (Jurnal Bisnis dan Akuntansi, 2006)
The purpose of this study is to investigate whether debt policy, dividend policy, institutional ownership, business risk, firm size, and earning volatility have significant influence to managerial ownership. This study uses an agency theory perspective as a based to do the research. Data were taken from all companies listed on Jakarta Stock Exchange over the three years period 2000-2002 using purposive sampling method. Only 23 companies meet the criteria and taken as samples for this study. SPSS 11.5 program is used in order to find out the significant influence from all independent variables above to managerial ownership as a dependent variable. Result of this research shows that only firm size has significant influence to managerial ownership, while other variables do not have significant influence to managerial ownership. But all independent variables together have significant influence to managerial ownership simultaneously.